Bitter melon juice exerts its efficacy against pancreatic cancer via targeting both bulk and cancer stem cells. Issue 9 (18th May 2018) - Dhar, Deepanshi; Deep, Gagan; Kumar, Sushil; Wempe, Michael F.; Raina, Komal; Agarwal, Chapla; Agarwal, Rajesh
Abstract : Pancreatic cancer (PanC) is one of the deadliest malignancies worldwide and frontline treatment with gemcitabine becomes eventually ineffective due to increasing PanC resistance, suggesting additional approaches are needed to manage PanC. Recently, we have shown the efficacy of bitter melon juice (BMJ) against PanC cells, including those resistant to gemcitabine. As cancer stem cells (CSCs) are actively involved in PanC initiation, progression, relapse and drug‐resistance, here we assessed BMJ ability in targeting pancreatic cancer‐associated cancer stem cells (PanC‐CSCs). We found BMJ efficacy against CD44 + /CD24 + /EpCAM high enriched PanC‐CSCs in spheroid assays; BMJ also increased the sensitivity of gemcitabine‐resistant PanC‐CSCs. Exogenous addition of BMJ to PanC‐CSC generated spheroids (not pre‐exposed to BMJ) also significantly reduced spheroid number and size. Mechanistically, BMJ effects were associated with a decrease in the expression of genes and proteins involved in PanC‐CSC renewal and proliferation. Specifically, immunofluorescence staining showed that BMJ decreases protein expression/nuclear localization of CSC‐associated transcription factors SOX2, OCT4 and NANOG, and CSC marker CD44. Immunohistochemical analysis of MiaPaCa2 xenografts from BMJ treated animals also showed a significant decrease in the levels of CSC‐associated transcription factors. Together, these results show BMJ potential in targeting PanC‐CSC pool and associated regulatory pathways, suggesting the need for further investigation of its efficacy against PanC growth and progression including gemcitabine‐resistant PanC.